Host-specific Dactylogyrus parasites revealing new insights on the historical biogeography of Northwest African and Iberian cyprinid fish - Šimková, Andrea; Benovics, Michal; Rahmouni, Imane; Vukić, Jasna (Parasites & vectors, 2017)
BACKGROUND: Host specificity in parasites represents the extent to which a parasite's distribution is limited to certain host species. Considering host-specific parasites of primarily freshwater fish (such as gill monogeneans), their biogeographical distribution is essentially influenced by both evolutionary and ecological processes. Due to the limited capacity for historical dispersion in freshwater fish, their specific coevolving parasites may, through historical host-parasite associations, at least partially reveal the historical biogeographical routes (or historical contacts) of host species. We used Dactylogyrus spp., parasites specific to cyprinid fish, to infer potential historical contacts between Northwest African and European and Asian cyprinid faunas. Using phylogenetic reconstruction, we investigated the origin(s) of host-specific Dactylogyrus spp. parasitizing Northwest African and Iberian cyprinid species. RESULTS: In accordance with hypotheses on the historical biogeography of two cyprinid lineages in Northwest Africa, Barbini (Luciobarbus) and Torini (Carasobarbus), we demonstrated the multiple origins of Northwest African Dactylogyrus. Dactylogyrus spp. of Carasobarbus spp. originated from Asian cyprinids, while Dactylogyrus spp. of Luciobarbus spp. originated from European cyprinids. This indicates the historical Northern route of Dactylogyrus spp. dispersion to Northwest African Luciobarbus species rather than the Southern route, which is currently widely accepted for Luciobarbus. In addition, both Northwest African cyprinid lineages were also colonized by Dactylogyrus marocanus closely related to Dactylogyrus spp. parasitizing African Labeo spp., which suggests a single host switch from African Labeonini to Northwest African Luciobarbus. We also demonstrated the multiple origins of Dactylogyrus spp. parasitizing Iberian Luciobarbus species. One Iberian Dactylogyrus group was phylogenetically closely related to Dactylogyrus of Moroccan Carasobarbus, while the second was related to Dactylogyrus of Moroccan Luciobarbus. CONCLUSIONS: Our study confirms the different origins of two Northwest African cyprinid lineages. It suggests several independent historical contacts between European Iberian Luciobarbus and two lineages of Northwest African cyprinids, these contacts associated with host switches of Dactylogyrus parasites.
Keywords: Host Specificity; Dactylogyrus; Phylogeography; Phylogeny; Cyprinids; fylogeografie; Biological Evolution; Host-Parasite Interactions; Platyhelminths; Asie; Northwest Africa; zvířata; Europe; Iberia; ploštěnci; Africa; hostitelská specificita; Host specificity; Afrika; fylogeneze; biologická evoluce; Asia; Animals; Historical biogeography; interakce hostitele a parazita; Evropa; Cyprinidae